2014
DOI: 10.1186/1476-069x-13-49
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-related air pollution and obesity formation in children: a longitudinal, multilevel analysis

Abstract: BackgroundBiologically plausible mechanisms link traffic-related air pollution to metabolic disorders and potentially to obesity. Here we sought to determine whether traffic density and traffic-related air pollution were positively associated with growth in body mass index (BMI = kg/m2) in children aged 5–11 years.MethodsParticipants were drawn from a prospective cohort of children who lived in 13 communities across Southern California (N = 4550). Children were enrolled while attending kindergarten and first g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(178 citation statements)
references
References 39 publications
7
168
2
1
Order By: Relevance
“…162 Prenatal air pollution exposures (PAHs, NO x , CO, PM) associated with birthweight have found either no associations or low birthweight, except for one report by Rundle et al, where prenatal exposures to PAHs were associated with obesity at age 7 years. 160,161,[163][164][165][166][167][168][169][170] Jerrett et al 162,171 examined the relationship between BMI levels in children and traffic density, air pollutants, and proximity of roadways to residential areas. In both studies, exposure to air pollutants resulted in increased BMI levels.…”
Section: Air Pollutionmentioning
confidence: 99%
“…162 Prenatal air pollution exposures (PAHs, NO x , CO, PM) associated with birthweight have found either no associations or low birthweight, except for one report by Rundle et al, where prenatal exposures to PAHs were associated with obesity at age 7 years. 160,161,[163][164][165][166][167][168][169][170] Jerrett et al 162,171 examined the relationship between BMI levels in children and traffic density, air pollutants, and proximity of roadways to residential areas. In both studies, exposure to air pollutants resulted in increased BMI levels.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Studies in Toronto have shown that exposure to traffic-related air pollution is associated with respiratory conditions (Buckeridge et al, 2002), increased risk of circulatory mortality (Jerrett et al, 2009), cardiovascular mortality (Chen et al, 2013), ischemic heart disease (Beckerman et al, 2012), and childhood atopic asthma (Shankardass et al, 2015). Research results in other locations have also shown associated negative health effects, such as asthma (Lin et al, 2002;McConnell et al, 2006), cancer and leukemia (Pearson et al, 2000) in children, and development of obesity in children (Jerrett et al, 2014). Exposure to traffic-related air pollution may also be associated with increased risk of dementia.…”
Section: Introductionmentioning
confidence: 98%
“…Three papers were derived from the Children's Health Study, a longitudinal survey conducted in 13 communities across Southern California in United States. Jerrett et al (2014) examined correlations among traffic density and traffic-related air pollution with increases in BMI in 4550 children aged 5e11 years. A 13.6% increase in annual BMI growth when comparing the highest to lowest tenth percentile of air pollution exposure was found, which resulted in an increase of nearly 0.4 BMI units on attained BMI at age 10.…”
Section: Discussionmentioning
confidence: 99%
“…Rundle et al (2012) found that maternal exposure to air polycyclic aromatic hydrocarbons (PAH) during pregnancy is positively correlated with increased body mass index (BMI) and obesity by age seven in children. A more recent study suggested that exposure to near-roadway pollution is also a contributing factor in the development of childhood obesity (Jerrett et al, 2014). Experimental evidence has revealed that ambient particle (diameter, <2.5 mm [PM 2.5 ]) exposure is capable of inducing metabolic abnormalities and obesity in non-human subjects (rodents) (Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%